(untitled) (Sains Humanika, 2012)
Reading the various types of information in the newspaper helps to shape and construct the teenagers’ minds. Although the newspaper has a variety of contents, it has not attracted the teenagers to accept it as one of the forms of their reading materials. With this in mind, the objectives of this study are to identify the types of news which are chosen by teenagers; and to investigate the need factors; which are associated with the teenagers’ acceptance to the newspaper. This study used the quantitative approach, with 387 respondents aged between 16 and 17 years old from national secondary schools Federal Territory Kuala Lumpur. The data of the study was analysed statistically by using Statistical Package for Social Science (SPSS) version 15.0. The two types of statistics used were descriptive statistics and inferential statistics. Descriptive statistics was used to identify percentage values, mean, average, and standard deviation. Inferential statistics was used to explain relationships between the variables studied. The results of the study found that the types of news, which are of the interest of the teenagers is the entertainment news. The result of the Pearson’s Correlation test shows that there is a positive and significant relationship between needs and acceptance. With reference to the results of the study, it is suggested that the teenagers’ need factors have to be maintained in each newspaper content. Hence, it is suggested to the newspaper institution to publish more of educational and informative materials in order to upgrade the teenagers’ understanding of a particular news.